ANALISIS DAMPAK MUTASI PADA SEMANGAT KERJA KARYAWAN PT. SEMEN BATURAJA TBK. - Safaruddin (Pojok Publisher, 2025)
The transfer of employee duties from one work unit to another within a company is a common occurrence, the main purpose of which is to increase company productivity by distributing human resources optimally. This research was conducted at PT Semen Baturaja Tbk. As one of the operating companies of the Semen Indonesia Group, it does the same thing by implementing employee transfers to other operating companies. The purpose of this research was to see how much impact mutations have on employee morale. This research uses a descriptive method supported by quantitative data analysis, where data was collected from respondents totaling 35 employees who were carrying out EOD (employees on duty) throughout 2024 (January-December period). The methods used to process and analyze the data are the Product Moment Correlation Test, Correlation Test, and Correlation Coefficient Significance Test (t-Test). This research arrived at results that show a real influence between mutations on work morale as seen from the magnitude of the correlation coefficient of 0.880 and the coefficient of determination value at 77.44%. This means that the mutation variable has an influence of 77.44%, while various other factors have an influence of only 22.56%. The significance test obtained a result of 10.643, so Ho is rejected and Ha is accepted. This means that the influence of mutation on employee morale has a significant influence.